Layout design as a risk driver for energy efficiency of photovoltaic power systems - Adrian Dumitru Tanţău; Horaţiu Regneală; Eliza Laura Coraş (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
This paper explores the existence of a correlation between the energy efficiency generated by photovoltaic power systems and the layout design of the photovoltaic panels, as well as the level in which the layout design acts as a risk driver for energy efficiency, in the context of solar energy. Improved energy efficiency is the decisive response to the weight of the climate change, limited conventional energy sources and technological innovation challenges with the purpose of carbon emissions reduction. However, the dangers hampering energy efficiency form a field of study less explored in the specific literature. As a result, in this paper, we seek to address the energy efficiency issue on the background of photovoltaic power systems, by focusing our attention on the technological parameters that influence it: the layout design of photovoltaic (PV) panels. Our methodology is based on a practical study performed over a period of one year on a photovoltaic field in Romania. The analysis was made with PV-syst software version 5.11., which helped us measure the photovoltaic system performance under three different variants, defined by the parameters that impact on the energy efficiency of the PV system. We have found that the generator inclination, the angle made by the panels shading horizontal distance and the distance between two consecutive rows of panels influence the power generated by the whole system, with direct effect on energy efficiency. The results of our study can guide a photovoltaic power system to boost its energy efficiency, while reducing the technological risks residing in practical manipulation of technical specification. This paper will contribute also to the literature of energy efficiency in the context of highly sought renewable energies by aligning technical parameters with performance ratios in a risk management and efficiency framework.
Keywords: 650; photovoltaic energy; energy efficiency; layout design; photovoltaic power system; PV panels